Phenomenological description of neutron yields from actinide fission - Lengyel, A.I.; Parlag, O.O.; Maslyuk, V.T.; Kibkalo, Yu.V. (Вопросы атомной науки и техники, 2011)
The phenomenological analysis of the neutron yields from the fission of ²³³U, ²³⁵U, ²³⁹Pu and ²⁵²Cf has been performed. The parameterization used allows the peculiarities of the 'sawtooth' curve of neutron multiplicity for light and heavy fragments to be described and predicted. Виконано феноменологічний аналіз виходів нейтронів з уламків поділу ²³³U, ²³⁵U, ²³⁹Pu та ²⁵²Cf. Вибрана параметризація та встановлені закономірності дозволяють описати та передбачити зміни "пилоподібної" поведінки виходу нейтронів з легкого та важкого уламків поділу ядер, які спостерігаються. Проведен феноменологический анализ выходов нейтронов из осколков деления ²³³U, ²³⁵U, ²³⁹Pu и ²⁵²Cf. Выбранная параметризация и установленные закономерности позволяют описать и предсказать наблюдаемые изменения 'пилообразного' поведения выхода нейтронов из легкого и тяжелого осколков деления ядер.